2005
DOI: 10.1128/aem.71.12.8663-8676.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gel-Pad Oligonucleotide Microarray Technology by Using Artificial Neural Networks

Abstract: Past studies have suggested that thermal dissociation analysis of nucleic acids hybridized to DNA microarrays would improve discrimination among duplex types by scanning through a broad range of stringency conditions. To more fully constrain the utility of this approach using a previously described gel-pad microarray format, artificial neural networks (NNs) were trained to recognize noisy or low-quality data, as might derive from nonspecific fluorescence, poor hybridization, or compromised data collection. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…One source of confusion might be the visible similarity of equilibrium dissociation curves in solution (30,31) to nonequilibrium dissociation curves, since both are sigmoid-shaped, but follow fundamentally different physical laws. Another source might be due to image acquisition software and processing errors, which have been shown to grossly distort signal intensity values, leading to misinterpretation of array data (10,32,33). Previously published literature does not provide any physicochemical proof that the NTD approach can be effectively used to distinguish between specific and nonspecific hybridizations for mixtures of targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One source of confusion might be the visible similarity of equilibrium dissociation curves in solution (30,31) to nonequilibrium dissociation curves, since both are sigmoid-shaped, but follow fundamentally different physical laws. Another source might be due to image acquisition software and processing errors, which have been shown to grossly distort signal intensity values, leading to misinterpretation of array data (10,32,33). Previously published literature does not provide any physicochemical proof that the NTD approach can be effectively used to distinguish between specific and nonspecific hybridizations for mixtures of targets.…”
Section: Discussionmentioning
confidence: 99%
“…We did not perform quantitative analysis of the curves published by Siripong et al . (35), since we have previously shown that the image processing algorithm used in their study significantly alters the signal intensities (10,32,33), making it impossible to analyze the chemical kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to get a lower limit of detection, many methods have been developed, including three-dimensional (3D) matrixes modification, such as Noble PA group and Bavykin S group developed ployacrylamide for surface modification [11,12], and Gershwin ME group and Dufva M group used agarose for surface coated and polymer [13,14], which could increase the efficiency of biomolecules immobilization. And some groups chose signal amplification technology [15][16][17][18][19], or used more sensitive signal detection and collection apparatus for signal collection.…”
Section: Tweenmentioning
confidence: 99%
“…This enables rapid establishment of the melting curves for all probes on the microarray, facilitating development of validated probe sets. Three-dimensional microarray systems include gel-pads [73,104,136], flow-through systems such as PamGene (www.pamgene.com) [192] or MetriGenix (www.metrigenix.com) [88].…”
Section: Three-dimensional Microarray Formatsmentioning
confidence: 99%